Sofosbuvir plus ribavirin and sofosbuvir plus ledipasvir in patients with genotype 1 or 3 hepatitis C virus and severe renal impairment: a multicentre, phase 2b, non-randomised, open-label study. (October 2020) - Lawitz, Eric; Landis, Charles S; Flamm, Steven L; Bonacini, Maurizio; Ortiz-Lasanta, Grisell; Huang, Jonathan; Zhang, Jie; Kirby, Brian J; De-Oertel, Shampa; Hyland, Robert H; Osinusi, Anu O; Brainard, Diana M; et al.
Summary: Background: There is a medical need for highly effective, safe, and well tolerated treatments for patients infected with hepatitis C virus (HCV) with severe renal impairment. We investigated the safety and efficacy of sofosbuvir with ribavirin or ledipasvir combined with sofosbuvir in a prospective study of patients with genotype 1 or 3 HCV infection and stage 4–5 chronic kidney disease (creatinine clearance by Cockcroft-Gault ≤30 mL/min) who were not on dialysis. Methods: This phase 2b, open-label, non-randomised, multicentre study in the USA and New Zealand investigated three sequentially enrolled cohorts of patients. Patients were recruited from ten hospitals and clinical research centres and were included if they had genotype 1 or 3 HCV infection, a creatinine clearance less than or equal to 30 mL/min, and were not on dialysis. In cohorts 1 and 2, patients received sofosbuvir (200 mg in cohort 1 and 400 mg in cohort 2) plus ribavirin 200 mg once per day for 24 weeks. In cohort 3, 18 patients received ledipasvir combined with sofosbuvir (90 mg ledipasvir and 400 mg sofosbuvir) once per day for 12 weeks. The primary efficacy endpoint was the proportion of patients achieving sustained virological response 12 weeks after the end of treatment (SVR12). Safety and pharmacokinetic data were also collected. The trial is registered with ClinicalTrials.gov, number NCT01958281, and is completed. Findings: This study was done between Oct 7, 2013, and Oct 29, 2017. In the sofosbuvir plus ribavirin cohorts, 32 patients were screened, of whom 20 were enrolled and assessed for efficacy and safety (ten patients in each cohort). In the ledipasvir plus sofosbuvir cohort, 33 patients were screened, of whom 18 were enrolled and assessed for treatment efficacy and safety. Four (40%, 95% CI 12–74) of ten patients in cohort 1 and six (60%, 26–88) of ten patients in cohort 2 achieved SVR12. All 18 (100%, 82–100) patients in cohort 3 achieved SVR12. Adverse events were mostly mild or moderate in severity. The most commonly reported adverse events overall were headache (eight [21%] of 38 patients), anaemia (seven [18%] of 38 patients), and fatigue (six [16%] of 38 patients). Eight patients had serious adverse events, none of which were treatment related. There were no treatment-related cardiac events or clinically significant changes in echocardiographic parameters or creatinine clearance by Cockcroft-Gault. Interpretation: In this phase 2b study, ledipasvir combined with sofosbuvir for 12 weeks was safe and effective in patients with genotype 1 HCV infection and stage 4–5 chronic kidney disease who were not on dialysis. Funding: Gilead Sciences.